Factors promoting breast, cervical and colorectal cancer screenings participation: A systematic review. Issue 9 (12th July 2022) - Vallone, Federica; Lemmo, Daniela; Martino, Maria Luisa; Donizzetti, Anna Rosa; Freda, Maria Francesca; Palumbo, Francesco; Lorenzo, Elvira; D'Argenzio, Angelo; Caso, Daniela
Abstract: Objective: The present study aims at systematically reviewing research conducted on factors promoting breast, cervical and colorectal cancer screenings participation. Methods: A literature search in MEDLINE/PubMed and PsycInfo from January 2017 to October 2021 was performed. Data extraction, researchers' full agreement and the inclusion criteria produced 102 eligible studies. Data were narratively synthesized and critically interpreted. Results: Multiple factors favoring or hindering breast, cervical and colorectal cancer screenings were identified and summarized as factors operating at the individual level (background information, individual characteristics, emotions related to screening procedure and to cancer, knowledge and awareness), at the relational level (relationships with healthcare staff, significant others, community members), and at the healthcare system level (systems barriers/policy, lack of staff). A critical appraisal of studies revealed a fragmentation in the literature, with a compartmentalization of studies by type of cancer screening, country and specific populations of destination. Conclusions: Overall findings indicated that greater integration of research results obtained independently for each cancer diagnosis and within the different countries/populations could foster a more comprehensive understanding of factors potentially enhancing the participation in breast, cervical and colorectal cancer screenings worldwide. This review, which is grounded in the current context of globalization and superdiversification in population, can help to enhance a better integration between research and practices, by supporting the development of more effective and inclusive evidence‐based interventions and health‐promotion campaigns worldwide. Research and practical implications are highlighted and discussed.